A influência política na gestão das empresas estatais à luz do direito fundamental à boa administração e da governança corporativa e pública - Santos, Flávio Rosendo dos (2015)
This study is dedicated to explain the extent to which political influence in the management of state-owned enterprises can be considered legitimate in the light of the fundamental right to good governance and corporate and public governance, for which was undertaken bibliographical and documentary research guided by the deductive method of work, in which were investigated and presented concepts and issues relating to the State, Government, politics, Public Administration, constitutional principles of Public Administration, the fundamental right to good administration, corporate and public governance and state enterprises. Based on the assumptions found in the works and consulted laws it was possible to conclude that the political influence in state-owned enterprises management can be considered legitimate in the light of the fundamental right to good governance if it promotes the public interest and the public purposes achievement, effectively, efficiently and if it preserves the citizens' rights and the principles and rules that make up the legal framework for public administration; and can be considered legitimate in the light of corporate and public governance to the extent that, in a transparent manner and according to the relevant rules, it seeks not the private benefit of politicians, but to promote the public interest or, in other words, the increase of public value produced by them, while protecting and guaranteeing the rights of its stakeholders and shareholders.